ChemInform Abstract: Rhodium‐Catalyzed Synthesis of 4‐Bromo‐1, 2‐dihydroisoquinolines: Access to Bromonium Ylides by the Intramolecular Reaction of a Benzyl Bromide and an α‐Imino Carbene. Issue 31 (14th July 2016) - He, Jun; Shi, Yinping; Cheng, Wanli; Man, Zengming; Yang, Dongdong; Li, Chuan‐Ying
Abstract: Highly functionalized isoquinolines are prepared from readily available aryl‐sulfonyl‐triazoles.